Uniaxial magnetic anisotropy in La0.7Sr0.3MnO3 thin films induced by multiferroic BiFeO3 with striped ferroelectric domains - You, Lu (2012)
Uniaxial magnetic anisotropy has been observed in La0.7Sr0.3MnO3 thin films grown on top of multiferroic BiFeO3 with ferroelectric stripe domains (see Figure). The magnetic easy axis of La0.7Sr0.3MnO3 correlates with the ferroelectric stripe domains. A possible spin coupling model at the La0.7Sr0.3MnO3/BiFeO3 interface is established between ferromagnetic and antiferromagnetic orders to explain this phenomenon.